Social and psychological technologies of information warfare and countermeasures - Beznosov, Dmitriy S. (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2025)
Introduction. The relevance of the problem of ensuring information security is substantiated. The purpose of the article is to analyze the socio-psychological ways of waging information warfare and the means of counteraction. Information warfare is a confrontation between the parties to a conflict with the help of disinformation. Objectives of the article are to prove that information influence is becoming a specific modern weapon; analyze ways to counter information warfare; describe the impact of information warfare on legal relations and legal consciousness. Theoretical analysis. Three types of war are analyzed: informational, cognitive and psychosensory. Information warfare is aimed at destroying the rule of law, legal relations and the state system of the enemy. Such a war can cause significant damage to the legal consciousness, forming distrust in the authorities. Information warfare has no borders and extends to the communication channels of all states. The conclusion of a truce or capitulation does not mean the end of the information war. The goal of cognitive warfare is to gain control over the op ponent’s mind, to recode his mentality. The tasks of psychosensory warfare include the suppression of the emotional state of members of society, the creation of an atmosphere of fear, horror, and hopelessness. In the course of such a war, terrorist acts are committed. Conclusion. The main method of counteraction is the consolidation of society, the preservation of one’s mentality and culture.